Resilient decentralised control of inverter‐interfaced distributed energy sources in low‐voltage distribution grids. Issue 2 (11th February 2020) - Nouri, Alireza; Soroudi, Alireza; Keane, Andrew
Abstract : This study shows that a relation can be found between the voltage at the terminals of an inverter‐interfaced renewable energy source (RES) and its optimal reactive power support. This relationship, known as volt–Var curve (VVC), enables the decentral operation of RES for active voltage management (AVM). Here the decentralised AVM technique is modified to consider the effects of the realistic operational constraints of RES. The AVM technique capitalises on the reactive power support capabilities of inverters to achieve the desired objective in unbalanced active low‐voltage distribution systems (LVDSs). However, as the results show, this AVM technique fails to satisfy the operator's objective when the network structure dynamically changes. By updating the VVCs according to the system configuration and components' availability, the objective functions will be significantly improved and the AVM method remains resilient against the network changes. To keep the decentralised structure, the impedance identification capability of inverters is used to locally find the system configuration. Adaptive VVCs enable the decentralised control of inverters in an online setting. A real‐life suburban residential LVDS in Dublin, Ireland, is used for showcasing the proposed method, and the effectiveness of the proposed resilient ACM technique is demonstrated.